Glycemic Index and Glycemic Load and Their Association with C-Reactive Protein and Incident Type 2 Diabetes - Geertruida J. van Woudenbergh; Anneleen Kuijsten; Eric J. G. Sijbrands; Albert Hofman; Jacqueline C. M. Witteman; Edith J. M. Feskens (Journal of Nutrition and Metabolism)
Objective. To investigate whether the Glycemic Index (GI) or Glycemic Load (GL) of a diet is associated with C-reactive Protein (CRP) and risk of type 2 diabetes in a prospective study. Materials and Methods. Our analysis included 4,366 participants who did not have diabetes at baseline. During follow-up 456 diabetes cases were confirmed. Dietary GI and GL were derived from a food-frequency questionnaire and its association with CRP was examined cross-sectionally using linear regression models. The association of GI and GL with diabetes incidence was examined using Cox proportional hazard models. Results. GL, but not GI, was associated with lnCRP at baseline (bGL=0.11 per 50 units; P=.01). When comparing the highest to the lowest tertile of GI with respect to diabetes incidence, a Relative Risk (RR) of 0.95 [95%CI 0.75, 1.21] was found after adjustment for lifestyle and nutritional factors. For GL the RR for diabetes incidence was 1.00 [95%CI 0.74, 1.36]. Additional adjustment for CRP did not change RRs. Conclusion. Since GI was not associated with CRP and risk of type 2 diabetes, it is unlikely that a high GI diet induces the previously shown positive association between CRP and risk of type 2 diabetes by increasing CRP concentrations.